1993
DOI: 10.1093/carcin/14.9.1881
|View full text |Cite
|
Sign up to set email alerts
|

High copper and iron levels and expression of Mn-superoxide dismutase in mutant rats displaying hereditary hepatitis and hepatoma (LEC rats)

Abstract: The LEC rat is a mutant strain displaying hereditary hepatitis and hepatoma. We established enzyme-linked immunosorbent assays of Cu,Zn- and Mn-superoxide dismutase (Cu,Zn- and Mn-SOD) and measured the levels of both SODs in various organs of LEC and Wistar rats. Mn-SOD concentrations were higher in LEC rats than in Wistar rats in most tissues. Cu,Zn-SOD levels of liver, kidney and intestine were lower in LEC rats than in Wistar rats. Atomic absorbtion techniques indicated that in addition to high Cu concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 0 publications
0
15
0
1
Order By: Relevance
“…This level, however, is not so high when compared to a copper accumulation that is 40-60 times higher in LEC rat liver, as compared to the Fisher rat liver as a control [7]. In contrast, levels of manganese in LEC rat liver are < 1 ⁄10 levels of Wistar rat liver [6]. These contrary changes may have an influence on levels of Cu, Zn-, and Mn-superoxide dismutases (SODs), which require metal ions as integral cofactors for enzymatic activities.…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…This level, however, is not so high when compared to a copper accumulation that is 40-60 times higher in LEC rat liver, as compared to the Fisher rat liver as a control [7]. In contrast, levels of manganese in LEC rat liver are < 1 ⁄10 levels of Wistar rat liver [6]. These contrary changes may have an influence on levels of Cu, Zn-, and Mn-superoxide dismutases (SODs), which require metal ions as integral cofactors for enzymatic activities.…”
mentioning
confidence: 69%
“…Abnormal hepatic iron accumulation is also observed in LEC rats [5,6]. Levels of iron concentrations in the liver of 18-week-old LEC rats reached up to three times those found in Wistar rat livers of the same age [6]. This level, however, is not so high when compared to a copper accumulation that is 40-60 times higher in LEC rat liver, as compared to the Fisher rat liver as a control [7].…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…[27][28][29] The amount of 8-OHdG in DNA is increased in the liver and kidney of LEC rats, 30) and the levels of Cu,Zn-superoxide dismutase, a specific scavenger of superoxide, in LEC rats are lower than those in Wistar rats, especially in the liver and kidney. 31) Copper and/or hemolysis-induced iron accumulation are considered to play roles in hepatocarcinogenesis in LEC rats, because copper-induced hemolysis occurs in the period of necrotizing hepatitis, and iron-deficient diet prevents the development of liver tumors. 32,33) In the present study, despite the diffuse periportal hemosiderosis of hepatocytes (data not shown) and the increased hepatic iron concentration the incidence of hepatocellular tumors in D-penicillamine-treated LEC rats was lower than that in controls, although we did not measure metal concentrations during the period of jaundice.…”
Section: Discussionmentioning
confidence: 99%
“…The Sod2 gene encodes an intramitochondrial free radical scavenging Mn-enzyme that is the first line of defense against superoxide produced as a toxic by-product of oxidative phosphorylation [3]. In this terms, it should be noted that the Mn-SOD levels in the LEC rat are lower than those of the normal control, especially in the liver and kidney [22], and that the amount of 8-hydroxydeoxyguanosine in DNA, a marker of active oxygen-derived DNA damage, is increased in the liver and kidney of the LEC rat [27]. These informations will help us to apply a positional candidate gene approach to clarify whether these genes are involved in the pathogenesis of renal cell carcinoma in the LEC rat.…”
mentioning
confidence: 99%